Description of two final stadium Onychogomphus larvae from Thailand (Odonata: Gomphidae) - Chainthong, Damrong; Boonsoong, Boonsatien (Zootaxa, 2016)
The final stadium larvae of Onychogomphus castor Lieftinck and O. duaricus Fraser are described and illustrated for the first time based on reared specimens from Thailand. The taxonomic characteristics of the larvae of the genus Onychogomphus are discussed and summarized. The larva of O. castor differs from other Southeast Asian species in having distinct mid-dorsal spines on S2–9, divergent wing pads reaching S5, and lateral spines on S6–9. The larva of O. duaricus has a weakly swollen third antennal segment, with short blunt mid-dorsal spines on S2–9, divergent wing sheaths reaching the middle of S4, and lateral spines present on S7–9.